The deposition kinetics of barium sulphate scale: model development - Rafiee, H.; Sorbie, K. S.; Mackay, E. J. (Frontiers in Materials, 2023)
The formation and deposition of mineral scales, such as barium sulphate (BaSO4) and calcium carbonate (CaCO3), is a common problem in many industrial and life science processes. This is caused by chemical incompatibility due either to the mixing of incompatible aqueous solutions or due to changes of the physical conditions, usually temperature and pressure. Many laboratory studies have been conducted using techniques broadly classified into batch and flowing tests to understand the reaction and mechanisms which occur in the initial stages of scale formation and its subsequent deposition on a solid surface. In this study we focused on the dynamic (kinetic) deposition of barium sulphate arising from the mixing of 2 incompatible brines, one containing barium (Ba2+) ions and other containing sulphate (SO42-) ions, suitably charged balanced by other inert anions and cations. . The mechanism of barium sulphate (barite) deposition is often assumed to be a one-step reaction in which the ions in the bulk fluid directly deposit onto a surface. However, there is strong evidence in the literature that barium sulphate may deposit through an intermediary nanocrystalline phase which we refer to as BaSO4(aq) in this paper. This initial nucleation species or nanocrystalline material (BaSO4(aq)) may remain suspended in the aqueous system and hence may be transported through the system before it ultimately is deposited on a surface, possibly covered by a previously deposited barite coating. This does not preclude the direct deposition of barite on the surface which may indeed also occur.